Is India's Economic Growth Leaving the Poor Behind? - Datt, Gaurav; Ravallion, Martin (World Bank, Washington, D.C., 2013)
There has been much debate about how much India's poor have shared in the economic growth unleashed by economic reforms in the 1990s. The authors argue that India has probably maintained its 1980s rate of poverty reduction in the 1990s. However, there is considerable diversity in performance across states. This holds some important clues for understanding why economic growth has not done more for India's poor. India's economic growth in the 1990s has not been occurring in the states where it would have the most impact on poverty nationally. If not for the sectoral and geographic imbalance of growth, the national rate of growth would have generated a rate of poverty reduction that was double India's historical trend rate. States with relatively low levels of initial rural development and human capital development were not well-suited to reduce poverty in response to economic growth. The study's results are consistent with the view that achieving higher aggregate economic growth is only one element of an effective strategy for poverty reduction in India. The sectoral and geographic composition of growth is also important, as is the need to redress existing inequalities in human resource development and between rural and urban areas.